Longitudinal SARS-CoV-2 antibody response in a healthcare worker cohort utilising the Abbott Alinity® anti-nucleocapsid assay. - Stephen P Connolly; Alejandro Garcia Leon; Sandra Green; Daragh McGee; Paul Duggan; Robert Browne; Sarah Miles; Riya Negi; Dana Alalwan; Dominick Natin; Patrick W Mallon; Peter O'Gorman; et al. (PLoS ONE)
Introduction Healthcare workers (HCWs) in Ireland bore a particularly high burden of SARS-CoV-2 infections, representing over 30% of infections during initial waves. We describe the prevalence, incidence and persistence of SARS-CoV-2 anti-nucleocapsid (anti-NC) IgG positivity in a cohort of HCWs working in a Dublin inner-city tertiary hospital, over 48 weeks. Methods The SORTeD (Seroprevalence, Seroconversion Rates and Transmission Dynamics of SARS-CoV-2 among Healthcare Workers) study was a longitudinal cohort study of HCWs working in an inner-city hospital in Dublin between July 2020 and September 2021. Participants had either a prior history of PCR-confirmed SARS-CoV-2 (Group 1) or no prior history of SARS-CoV-2 (Group 2). Serum samples were obtained at weeks 0, 12 and 48, and tested for SARS-CoV-2 nucleocapsid (NC) antibody using a qualitative immunoassay (Abbott Alinity®). Seroprevalence rates are presented using descriptive statistics, with univariate and multivariate analysis examining associations between participant characteristics, IgG status and refractive index in Group 1. Data is presented as n (%) or median (interquartile range (IQR)) where appropriate. Results Of the 395 HCWs who were recruited, 304 (77.0%) were female, median age was 33 (28-45) years, and 343 (86.8%) had patient-facing roles. In Group 1, time from infection to sampling was 173 (144.0-202.0) days. Seroprevalence of IgG in Group 1 at 0, 12 and 48 weeks was 47.4%, 19.0% and 7.3%, respectively; while seroprevalence in Group 2 was 5.4%, 4.3% and 2.6%, respectively. A lower refractive index was seen in higher sampling intervals (r = -0.5, 95% CI -0.576 to -0.427; p < 0.001). Fourteen incident infections were reported by the cohort during the study, and 3 documented reinfections. Conclusion Our study shows low seroprevalence in prior confirmed cases among our HCW population, possibly explained by reduced sensitivity of this assay with increasing time from SARS-CoV-2 exposure and timing of testing. Confirmatory testing with a quantitative assay would help understand the true seroprevalence of SARS-CoV-2 IgG in this cohort.